Beyond the medieval village the diversification of landscape character in southern Britain - Rippon, Stephen, 1968- (Medieval history and archaeology., 2008)
Stephen Rippon explores the origins of regional variations in the character of the landscape of southern Britain, arguing that while some landscapes date back to the centuries either side of the Norman Conquest, other areas across southern Britain underwent a profound change around the 8th century AD.